2017
DOI: 10.1371/journal.pone.0177591
|View full text |Cite
|
Sign up to set email alerts
|

Plant cell wall glycosyltransferases: High-throughput recombinant expression screening and general requirements for these challenging enzymes

Abstract: Molecular characterization of plant cell wall glycosyltransferases is a critical step towards understanding the biosynthesis of the complex plant cell wall, and ultimately for efficient engineering of biofuel and agricultural crops. The majority of these enzymes have proven very difficult to obtain in the needed amount and purity for such molecular studies, and recombinant cell wall glycosyltransferase production efforts have largely failed. A daunting number of strategies can be employed to overcome this chal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…Previous studies demonstrated that the fiber strength commonly related to the strengthening of cell wall 59 . Interestingly, identification of cell wall related genes such as ABC transporter-like 47 , 60 , 61 , arabinogalactan peptide (AGP) 62 , 63 , alpha-1,4-glucan-protein synthase 64 , calcium-binding EF-hand protein 61 , cellulose synthase 63 , glutathione peroxidase 65 , glycoside hydrolase 66 , glycosyl transferase 67 69 , extensin 62 , UDP-glucuronosyl/UDP-glucosyltransferase 70 , small GTPase superfamily 71 , kinesin 72 , leucine-rich repeat 61 , thaumatin 73 , tubulin 74 , and WD40 repeat 75 in PCoEGs and NCoEGs, emphasizing their potential roles in regulating cell wall integrity and thus fiber quality (Supplementary Dataset S8). However, the detailed molecular investigation is needed further to establish a link between CAMTAs and fiber quality traits.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that the fiber strength commonly related to the strengthening of cell wall 59 . Interestingly, identification of cell wall related genes such as ABC transporter-like 47 , 60 , 61 , arabinogalactan peptide (AGP) 62 , 63 , alpha-1,4-glucan-protein synthase 64 , calcium-binding EF-hand protein 61 , cellulose synthase 63 , glutathione peroxidase 65 , glycoside hydrolase 66 , glycosyl transferase 67 69 , extensin 62 , UDP-glucuronosyl/UDP-glucosyltransferase 70 , small GTPase superfamily 71 , kinesin 72 , leucine-rich repeat 61 , thaumatin 73 , tubulin 74 , and WD40 repeat 75 in PCoEGs and NCoEGs, emphasizing their potential roles in regulating cell wall integrity and thus fiber quality (Supplementary Dataset S8). However, the detailed molecular investigation is needed further to establish a link between CAMTAs and fiber quality traits.…”
Section: Discussionmentioning
confidence: 99%
“…First, protein purification for biochemical activity assay has only been accomplished in few cases due to the labile nature and low abundance of these enzymes [ 12 , 13 ]. Heterologous expression in E. coli has been largely ineffective, likely limited by insufficient folding and post-translational modification in bacterial systems [ 14 16 ]. Heterologous expression in eukaryotic systems has been reported, but no generally successful system has been found.…”
Section: Introductionmentioning
confidence: 99%
“…Escherichia coli is most often used. In general, expression is low (≤10 mg/L; e.g., Arend, Warzecha, Hefner, & Stöckigt, 2001;Schmölzer, Gutmann, Diricks, Desmet, & Nidetzky, 2016) and poor (≤1 mg/L) in various instances (e.g., Cai et al, 2017;Welner et al, 2017). With notable exceptions (Arend et al, 2001;Dewitte et al, 2016;Priebe, Daschner, Schwab, & Weuster-Botz, 2018;Schmideder et al, 2016), the enzyme production has received relatively little attention for systematic process development.…”
Section: Introductionmentioning
confidence: 99%